Commissary General of Musters Office and successors, General muster books and pay lists, Infantry, 49th Foot, 1st Battalion (Princess Charlotte of Wales') (WO 12/6033-6045) (Records of the Public Record Office.)
Muster rolls record the name, rank, military station and pay period for each soldier while they were with the regiment. WO 12/6033-6045 covers the 49th Regiment of Foot (i.e. Princess Charlotte of Wales's (Royal Berkshire) Regiment), 1798-1816.